Proceedings of Light-Activated Tissue Regeneration and Therapy Conference - Waynant, Ronald; Tata, Darrell B. (Lecture Notes in Electrical Engineering, 2008)
The Proceedings of the Light-Activated Tissue Regeneration and Therapy Conference covers the latest advances in the field including measurements that help determine the mechanisms of light-activated tissue regeneration and therapy. It also covers light sources that include lasers, LEDs, two wavelength sources, broadband sources and the metrology and medical outcomes they produce. These proceedings offer a systematic approach to the field of Light-Activated Tissue Regeneration and Therapy covering theory, basic research and clinical studies. Topics covered by leading medical experts and researchers include extensive papers and coverage on such interesting topics as: Pain Wound healing Diabetes Cardiovascular and stroke repair Neuroscience / progenitor and stem cells Dental About the Editors: The Editor of the proceedings, Ronald W. Waynant Ph.D., is a Senior Optical Engineer with the Food and Drug Administration Center for Devices and Radiological Health in Silver Spring, MD, and an Adjunct Associate Professor with the Uniformed Services University in Bethesda, MD. He previously served as an Adjunct Professor of Electrical Engineering at Catholic University. Dr. Waynant previously served as the Editor-in-Chief of IEEE Circuits and Devices Magazine and is a Fellow of The American Institute of Medical and Biological Engineers, The IEEE, The Optical Society of America, and The American Society for Laser Surgery and Medicine. Darrell Tata, Ph.D. is a senior biophysicist working at the FDA on non-invasive therapeutics through the application of physical techniques of optical and near infra-red light on biological systems. His current research is in the applications of non-ionizing radiation in obtaining desired biological activation and therapeutic response in several serious human diseases / ailments, notably, malignant cancers, diabetes, and chronic pain. Dr. Tata has conducted research at the University of Illinois at Urbana-Champaign (Dept. of Physiology and Biophysics), Stanford University (Dept. of Radiation Oncology), University. of Vermont (Dept. of Pharmacology), and the Mayo Clinic (Dept. of Urology). .